Method for Combining Information from White Matter Fiber Tracking and Gray Matter Parcellation - Park, Hae-Jeong; Kubicki, Marek; Westin, Carl-Fredrik; Talos, Ion-Florin; Brun, Anders; Peiper, Steve; Kikinis, Ron; Jolesz, Ference A.; McCarley, Robert W.; Shenton, Martha E. (American Journal of Neuroradiology, 2004)
Summary: We introduce a method for combining fiber tracking from diffusion-tensor (DT) imaging with cortical gray matter parcellation from structural high-spatial-resolution 3D spoiled gradient-recalled acquisition in the steady state images. We applied this method to a tumor case to determine the impact of the tumor on white matter architecture. We conclude that this new method for combining structural and DT imaging data is useful for understanding cortical connectivity and the localization of fiber tracts and their relationship with cortical anatomy and brain abnormalities.